Judges Considerations of Criminal Acts Conducted By Adult against Children - Siska Septiyanti; Achmad Sulchan (Law Development Journal, 2020)
Children are one of the assets of national development, which should be considered and taken into account in terms of quality and their future. Without reliable quality and a clear future for children, national development and the fate of the nation will be difficult to imagine. Children, as heirs and holders of the fate of the nation, also determine the pace of the national development process in all fields. The formulation of the problem is 1) How is the Law on Judicial Power in making considerations? 2) How to overcome the obstacles and solutions given by the Judge in giving consideration to the crime of decency committed by adult men against children? The method used is juridical normative. The results of this study are: (1) The judges' consideration of decency crimes committed by adult men against minors in the decision of the Temanggung District Court Number: 53/Pid.Sus/2019/PN TMG has paid attention to the basis for judging, the basis for deciding, and values who live in society, then have considered juridical considerations. (2) Overcoming obstacles and solutions given by judges in giving consideration to crimes of decency committed by adult men against children.